Association Between Left Atrial Stiffness Index and Atrial Fibrillation Recurrence in Patients Undergoing Left Atrial Ablation. (March 2016) - Khurram, Irfan M.; Maqbool, Farhan; Berger, Ronald D.; Marine, Joseph E.; Spragg, David D.; Ashikaga, Hiroshi; Zipunnikov, Vadim; Kass, David A.; Calkins, Hugh; Nazarian, Saman; Zimmerman, Stefan L.
Abstract : Background—: Atrial fibrillation (AF) is associated with significant abnormalities of left atrial (LA) systolic and diastolic function. This study describes a novel measure, LA stiffness index, that estimates LA diastolic function and its association with clinical outcomes of catheter ablation. Methods and Results—: A total of 219 AF patients referred for ablation (59% paroxysmal, mean CHA2 DS2 VASc score 1.7±1.4) were enrolled. Atrial pressure and volume loops were prepared from invasive pressure measures and cardiac magnetic resonance imaging volumetric data during sinus rhythm for all patients. An LA stiffness index was created, defined by the ratio of change in LA pressure to volume during passive filling of LA (ΔP/ΔV). Patients were followed prospectively. Mean LA stiffness index for AF patients was 0.6±0.5 mm Hg/mL (paroxysmal AF 0.51±0.4 and persistent AF 0.73±0.6; P <0.001). Linear regression analysis showed a rise in the stiffness index with age, increasing at a rate of 0.02 mm Hg/mL per year ( P <0.001). The LA stiffness index was higher in patients with previous LA ablation(s) for AF (0.51±0.35 versus 0.83±0.70; P <0.001). Forty of 160 patients had recurrence after AF ablation with a mean follow-up of 10.4±7.6 months. Patients with recurrence had higher stiffness index than those without recurrence (0.83±0.46 versus 0.40±0.22; P <0.001). Conclusions—: LA stiffness index, a novel measure to assess LA diastolic function, increases with age and is higher in persistent AF and in the setting of repeat AF ablation. Greater LA stiffness index was independently associated with recurrence of AF after LA ablation.